Development of Comic Media for PJOK Subject on "The Dangers of Smoking at School Age" for Grade V Student’s at SDN 29 Cakranegara - Wijaya, Tami Amalia; Erfan, Muhammad; Zain Amrullah, Lalu Wira; Dwina Angga, Prayogi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This research aims to develop comic-based media on the topic of Physical Education, Sports, and Health (PJOK) on the topic of the dangers of smoking for fifth-grade student’s at SDN 29 Cakranegara. The research method used is research and development (R&D) with the ADDIE model approach, which includes analysis, design, development, implementation, and evaluation. This study involves all fifth-grade student’s at SDN 29 Cakranegara, consisting of 25 student’s and 1 teacher. The result of this research is a PJOK comic media that contains material about the dangers of smoking for school-age children. This comic is comprehensively structured with a title, usage instructions, main material, and exercise questions. Based on validation by media experts, this comic obtained an average feasibility percentage of 82.22%, and subject matter expert, it received 89.3%. Additionally, the results of small and large-scale trials, involving responses from teachers and student’s, indicate that this comic media falls into the very feasible category. This PJOK comic media can be used as a learning tool for the dangers of smoking, attracting student’s interest in learning, increasing learning motivation, and enhancing student’s knowledge and understanding of the dangers of smoking.